Performance evaluation of maize in Jumla district of Nepal: from yielding perspective - Jiban Shrestha (Hasanuddin University, 2019)
The performance evaluation of maize genotypes at a specific growing region is a key to crop improvement. The objectives of this study were to evaluate grain yield of maize genotypes at Bijayanagar (Mahatgaun VDC) and Tallo Lorpa (Dillichaur VDC), Jumla District of Nepal during spring seasons of 2012 and 2013. The maize genotypes were significant (P< 0.05) for grain yield, days to tasseling and silking and disease scoring where as anthesis-silking interval, plant height and ear height were non significant. The pooled analysis of the results showed that the highest grain yield was produced by Ganesh-1 (4830 kg/ha) followed by KKT-POP (4408 kg/ha), KKT-14 (3952 kg/ha) and MGU-08 (3913 kg/ha, respectively. From this study, Ganesh-1, KKT-POP, KKT-14 and MGU-08 could be preferable choice for cultivation in Jumla district of Nepal.